ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS DAN MINAT BELAJAR SISWA SMP PADA MATERI SEGITIGA DAN SEGIEMPAT - Nuron, Nuron; Sopandi, Dede; Sari, Veny Triyana Andika (IKIP Siliwangi, 2018)
The purpose of this study is to analyze the ability of mathematical communication and student learning interest and describe it especially on triangle and quadrilateral material on the students of class VII PGRI 168 Cikalongwetan Junior High School. The research method used is descriptive qualitative. The subjects studied are class VII SMP PGRI 168 Cikalongwetan consisting of 6 people. The instrument used in the form of a written test that contains 5 items about mathematical communication and 25 students questionnaire scale student interest. The results were tested statistically using SPSS IDM software version 21 to find normality and correlation using product moment person. Data validity is done by triangulation technique and source triangulation. The results of the research show that there is a relationship that interplay between the ability of mathematical communication and student learning interest.